Conceptualizing Physical Literacy within an Ecological Dynamics Framework. Issue 4 (1st October 2020) - O'Sullivan, Mark; Davids, Keith; Woods, Carl T.; Rothwell, Martyn; Rudd, James
ABSTRACT: Currently, there are numerous definitions and interpretations of the concept of physical literacy within the literature, potentially leading to a lack of consensus as to how to employ it in practice. In this position paper, we argue that ecological dynamics is well positioned to provide a theoretical framework that will bring clarity as well as support the operationalization of physical literacy in practice. We argue that this theoretical conceptualization provides an excellent framework for understanding physical literacy because of its emphasis on the person–environment relationship. More directly, we propose the establishment of an individual-environment fit across varied movement contexts over a lifespan as a central tenet of the physical literacy concept. We conclude by discussing how sports practitioners, national governing bodies, public health, and education sectors could re-design sport, exercise, and physical activity environments, in accordance with an ecological dynamics rationale to enhance physical literacy.